1967
DOI: 10.2172/12514216
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of Heme Synthesis: Studies on Erythrocyte Aminolevulinic Acid Synthetase

Abstract: The synthesis of aminolevulinic acid (ALA) is the first in a series of enzymatic reactions leading to the formation of tetrapyrrols and heme. The reactions shown on this slide as well as the final two steps in heme synthesis are localized within mitochondria. This fact has implicated the synthesis of ALA as the site of a feedback control mechanism whereby heme synthesis may be regulated i and integrated with the formation of other parts of the hemoglobin molecule. The following studies were performed: (1) to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1968
1968
1973
1973

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…They found the most striking effects were observed in precursor cells derived from animals rendered iron deficient by diet or phlebotomy. The increased formation of globin secondary to haem synthesis is in keeping with the hypothesis of the control and co-ordination of the synthesis between haem and globin (Vavra 1967).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…They found the most striking effects were observed in precursor cells derived from animals rendered iron deficient by diet or phlebotomy. The increased formation of globin secondary to haem synthesis is in keeping with the hypothesis of the control and co-ordination of the synthesis between haem and globin (Vavra 1967).…”
Section: Discussionsupporting
confidence: 84%
“…Recently it has been shown that the characteristic disorder in this disease is a defect in the rate of synthesis of either the alpha or beta chain with diminished formation of globin (Bank & Marks 1966). Since there is apparently a regulatory mechanism for haem formation by globin (Vavra 1967) diminished globin synthesis will reduce the formation of haem. The disproportionately low specific activity of glycine-2-I4C in haem as compared to that in globin can be explained by the striking reduction in ALA synthesis and haem synthesis enzymes in bone marrow aspirates from four patients with thalassaemia major (Steiner et al 1964).…”
Section: Discussionmentioning
confidence: 99%
“…Aoki et al (1971) reported an inhibitory effect of ferrous iron on partially purified ALA synthetase from rabbit reticulocytcs. However, in chicken reticulocyte mitochondria iron had an enhancing effect on ALA syiithetasc activity (Vavra, 1967) and in rabbit mitochondria, ferrous iron had no effect on ALA synthetase activity in concentratioiis ranging from 1.7x I O -~ to 1.7x I O -~ M (Bottomley & Smithee, 1968).…”
Section: Discussionmentioning
confidence: 92%